Indagando o perfil de tradutores em formação: um estudo de caso - Camila Nathalia de Oliveira Braga (2007)
This thesis presents a case study investigating translation students with a view to characterizing their performance in the novice-expert translator continuum. The study followed five undergraduate students enrolled for the course (Tradução II), at Faculdade de Letras/UFMG, who were requested to do three translation tasks: one taking place at the beginning of the course, another one in the middle and the final one at the end of the course. For each task, a complete and/or independent text originally written in English was selected, each one belonging to a different text type and being in a sequence of progressive complexity regarding logic-semantic relations (HALLIDAY & MATTHIESSEN, 2004). This progression was established according to the number of projections in the three texts (0, 3 and 12, respectively). In order to investigate the subjects profile, the first research question aimed at verifying which data can be gathered through the analysis of text production focusing on clause complexes that were considered problematic in view of the number and extension of pauses registered during the translation task. This verification was made through the analysis of some units associated to longer pauses during the tasks because of the multiple choices of taxis and logic-semantic relations (HALLIDAY & MATTHIESSEN, 2004) they contained. The second question aimed to verify data related to time allocated to each phase of the translation process (JAKOBSEN, 2002, 2003), instances of metalanguage and metareflection (ALVES, 2005; ALVES & GONÇALVES, 2007) in verbal protocols and search strategies used by the students. The third question aimed to observe the impact of the course on the subjects translation process and product through data obtained from verbal protocols, related to the subjects perception of the relevance of the course contents and its application in the actual practice of text analysis during the three tasks. Results allowed to locate the subjects in different stages of the novice-expert translator continuum according to their profile: three subjects presented a profile that can be located in an intermediary stage of the continuum, while the other two presented a profile that is clearly similar to the profile pointed by the literature as novice translators. Analysis of text production focusing problem resolution caused by clause complexes showed little metareflection and absence of metalanguage drawing on a linguistic theory that could allow the subjects to formulate the problems they encountered. Data concerning the subjects cognitive rhythm were not easily relatable to the two distinct profiles of the groups, showing that orientation and revision times cannot be taken as criteria necessarily linked to a particular type of performance. As regards the impact of the course contents, mainly devoted to text analysis, this study shows that some of the concepts discussed in class appear in the subjects verbal protocols, even though their performance in the translation tasks did not seem to have undergone substantial changes from one to the other.